A Biblical Point of view on Homosexuality - Anderson, J. Kerby (Eugene Harvest House Publishers, 2008)
In the last few decades, homosexuality has moved from the margins of society to the mainstream. In response to this cultural shift, Christian apologist and radio host Anderson sorts through myths to deliver the facts on homosexuality and the impact it has.
Keywords: Homosexuality -- Religious aspects -- Christianity. Homosexualité -- Aspect religieux -- Christianisme